MEMBANGUN PENDIDIKAN INKLUSIF: ANALISIS ISU-ISU MULTIKULTURAL DALAM DUNIA PENDIDIKAN INDONESIA - Aslinda, Aslinda; Amrizon (Midaduna: Journal of Islamic Studies, 2025)
Multicultural education has become a crucial discourse in addressing the challenges of ethnic, religious, cultural, and linguistic diversity in Indonesia. Although various efforts have been made to integrate multicultural principles into curricula and educational practices, several issues still hinder the creation of inclusive and equitable education. This article aims to analyze key issues in multicultural education, including discrimination, curriculum bias, unequal access, and the lack of teacher training in managing diversity. This study employs a descriptive qualitative method with literature review and policy document analysis as its main approach. The analysis reveals that although national policies support multicultural values, implementation at the grassroots level still shows significant gaps, particularly in peripheral schools and conflict-prone areas. Educational reform and competency-based multicultural teacher training are urgently needed to create a learning environment that respects diversity. This article is expected to contribute to academic discourse in promoting the development of just and equitable education amid Indonesia's diverse society.